EFFECTS OF RELAXATION THERAPY USING MUSIC ON BREAST MILK PRODUCTION IN POSTPARTUM MOTHERS - Widyantari, Kadek Yuke; Dasuki, Djaswadi; Daryanti, Menik Sri (LPPM Universitas Prima Nusantara Bukittinggi, 2020)
Introduction: Low milk production is one of the main reasons mothers do not provide breast milk exclusively. Relaxation therapy interventions are expected to help increase milk production. Purpose: The purpose of this scoping review is to map available evidence related to the effect of relaxation therapy interventions on breast milk production in postpartum mothers. Methods: In this scoping review, the authors identify studies that explain the effect of relaxation therapy on breast milk production in postpartum mothers from three databases (PubMed, Wiley, and Science Direct). Searches are limited to studies published in English and present data for the period 2010-2019. The identified research was reviewed using the PRISMA Flowchart. Studies with quantitative designs related to the effect of relaxation therapy on the production of breast milk are then selected for review. Results: From a total of four articles that have been reviewed, two sub-themes are found, relaxation therapy increases milk production (increased success of breastfeeding, increased milk secretion and fat content in breast milk), and relaxation therapy decreases maternal stress levels (reduces stress scores and cortisol levels). Conclusion: From this review, some evidence shows music therapy is effective in significantly increase milk production. All studies included in the analysis have limitations related to the research design or sample collection procedures. The method of relaxation therapy is simple, inexpensive, and easy to use without the involvement of hospital staff. Regarding the intervention, all the intervention groups in this study showed a significant effect compared to the control group.